2020
DOI: 10.3389/fbioe.2020.00499
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo Comparison Study Between Strontium Nanoparticles and rhBMP2

Abstract: The osteoinductive property of strontium was repeatedly proven in the last decades. Compelling in vitro data demonstrated that strontium hydroxyapatite nanoparticles exert a dual action, by promoting osteoblasts-driven matrix secretion and inhibiting osteoclasts-driven matrix resorption. Recombinant human bone morphogenetic protein 2 (rhBMP2) is a powerful osteoinductive biologic, used for the treatment of vertebral fractures and critically-sized bone defects. Although effective, the use of rhBMP2 has limitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…It has better clinical application than recombinant human BMP-2, another osteoinductive biologic material. 190 Sr-doped HA scaffolds increase local Sr 2+ concentrations and exhibit specific effects on osteoblasts and osteoclasts. 191 Tests have demonstrated their excellent osteoconductive, osteoconductive, and osseointegration properties in vitro.…”
Section: Application Of Sr In Osteogenic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has better clinical application than recombinant human BMP-2, another osteoinductive biologic material. 190 Sr-doped HA scaffolds increase local Sr 2+ concentrations and exhibit specific effects on osteoblasts and osteoclasts. 191 Tests have demonstrated their excellent osteoconductive, osteoconductive, and osseointegration properties in vitro.…”
Section: Application Of Sr In Osteogenic Scaffoldsmentioning
confidence: 99%
“…Sr‐doped HA scaffolds can continuously release Sr 2+ for more than 28 days and promote endochondral ossification, inhibiting osteoclasts' activity. It has better clinical application than recombinant human BMP‐2, another osteoinductive biologic material 190 . Sr‐doped HA scaffolds increase local Sr 2+ concentrations and exhibit specific effects on osteoblasts and osteoclasts 191 .…”
Section: Mechanism Of Single Alkaline Earth Metal In Osteogenesis And...mentioning
confidence: 99%
“…Many biological investigations were carried out on this doping ion, in particular by verifying its interaction with osteoblast-like cells and human osteoclasts to verify proliferation or inhibition, osteogenic differentiation, and angiogenic factor expression. It has been concluded that the bone cell behaviour is Sr 2+ -ion-dose dependent [ 20 , 21 , 22 ]. It was also shown that Sr doping can stabilise the HA crystal which affects, on the one hand, the mechanical stability of the new bone and, on the other hand, also increases the hardness of ceramic scaffold [ 23 , 24 ].…”
Section: Bioactive Ion-doped Nanohydroxyapatitesmentioning
confidence: 99%
“…Sr is an important component of bone. It plays a key role in bone integration by promoting osteoblast differentiation and accelerating bone formation, while inhibiting osteoclast differentiation and reducing bone resorption ( Choudhary et al, 2007 ; Bonnelye et al, 2008 ; Montagna et al, 2020 ). Sr-containing drugs play an active role in clinical application for anti-osteoporosis.…”
Section: Introductionmentioning
confidence: 99%